PERANCANGAN GAME SIMULASI PENGENALAN PERANGKAT KERAS CPU MENGGUNAKAN APLIKASI SCRATCH 3 PADA SISWA KELAS X TKJ SMK - Roziq, Fahrul Arifatul; Fajriani, Alfiah; Razilu, Zila (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to develop an interactive 2D learning media based on Scratch 3 to assist tenth-grade TKJ students at SMKN 1 Kendari in understanding the components of a computer CPU motherboard. The background of this research lies in the low level of student interest in learning computer hardware, as the teaching methods are still predominantly lecture-based and less interactive. Therefore, innovative media are required to provide a more engaging and enjoyable learning experience. The development model employed is ADDIE, which includes the stages of needs analysis, design, media development using Scratch 3, implementation through conversion into HTML and Android application formats, and evaluation through expert validation and user testing. The validation results indicate that the average assessment from media experts reached 85.8% in the good category, while material experts obtained an average score of 87.5% in the very good category. User trials involving 30 students resulted in an overall average score of 89.1% categorized as very good, where the visual aspect achieved 85.0% good, while interactivity, ease of use, clarity of material, device compatibility, and learning motivation reached 90.0% (